Ontogeny and Structure of the Pericarp of Schinus terebinthifolius Raddi (Anacardiaceae) - Carmello-Guerreiro, Sandra Maria; Paoli, Adelita Aparecida Sartori [UNESP] (Brazilian Archives of Biology and Technology, 2002)
O fruto de Schinus terebinthifolius Raddi é uma drupa vermelha, globosa, com exocarpo friável quando maduro e composto de duas camadas lignificadas: a epiderme e a hipoderme. O mesocarpo é parenquimático com grandes canais secretores associados aos feixes vasculares. No mesocarpo distinguem-se duas regiões uma externa composta apenas de células parenquimáticas e uma interna, delimitada por uma ou mais camadas de células contendo cristais de oxalato de cálcio do tipo drusa, composta de células parenquimáticas, canais secretores e feixes vasculares. O mesocarpo desprende-se do exocarpo devido à degeneração das camadas celulares em contato com a hipoderme. O endocarpo é lignificado e composto de quatro camadas: uma mais externa de células poliédricas com cristais prismáticos de oxalato de cálcio e três mais internas de esclereides em paliçada.

The fruit of Schinus terebinthifolius Raddi is a globose red drupe with friable exocarp when ripe and composed of two lignified layers: the epidermis and hypodermis. The mesocarp is parenchymatous with large secretory ducts associated with vascular bundles. In the mesocarp two regions are observed: an outer region composed of only parenchymatous cells and an inner region, bounded by one or more layers of druse-like crystals of calcium oxalate, composed of parenchymatous cells, secretory ducts and vascular bundles. The mesocarp detaches itself from the exocarp due to degeneration of the cellular layers in contact with the hypodermis. The lignified endocarp is composed of four layers: the outermost layer of polyhedral cells with prismatic crystals of calcium oxalate, and the three innermost layers of sclereids in palisade.
Keywords: Anacardiaceae; Schinus terebinthifolius; pericarp; anatomy; pericarpo; anatomia